Developing a Disease Resistant Cow - International Livestock Research Institute (International Livestock Research Institute, 2010)
Though this research still has a long way to go before it will benefit farmers, the resulting cows could potentially be more productive and safer than current animals. Recorded at the ILRI Annual Program Meeting, Addis Ababa, 14-17 April 2010.